Estimation of Eyeball Volume using computed tomography in a sample of Libyan population - Alshokri , Seleema; Ahmed El Obeidi, Adel (Benghazi University Medical Journal, 2024)
Background: A few ocular illnesses that change the eye’s dimensions may cause visual anomalies such as myopia, hypermetropia, presbyopia,macrophthalmia, microphthalmia, and astigmatism. In accordance, the knowledge of eyeball volume is mandatory; its significant is quite clear in understanding illnesses such as Coats’ disease, phthisis bulbi, and persistently hyperplastic primary vitreous that are linked to decreased ocular volume. Aim: This study aims to evaluate eyeball volume using computed tomography in a Libyan population to be used as a reference in diabetic retinopathy (DR) and macular edema screening programs. Patients & Methods: This is a retrospective study of the CT medical records of 100 consecutive subjects aged 20 to 80 years who were scanned in the diagnostic radiology department of the National Cancer Center, of Benghazi (NCCB) for different causes during the period from December 2023 to April 2024. Results: This study included 100 patients; 63 (63%) were males, and 37 (37%) were females. The mean age was 43.12 ± 25.24 years for males and 41.24 ± 31.73 years for females. There was no statistically significant difference in the mean age between both sexes. There was no statistically significant difference in the mean eyeball volume for both sexes concerning age. The right eyeball volume was higher for both males and females. Conclusion: Ocular volume correlated positively with the age of the patients, and males had slightly larger eyeballs compared to females. This data might be useful in ophthalmological, oculoplastic, and neurological practice. The right eyeball volume was higher on the right for both males and females.